Interviewing people with dementia in hospital: recommendations for researchers. Issue 7 (16th February 2016) - Digby, Robin; Lee, Susan; Williams, Allison
Abstract : Aims and objectives: This article aims to: Discuss the inclusion of the perspectives of people with dementia in research. Consider the major challenges involved in the process of interviewing people with dementia. Provide recommendations for those involved in interviewing people with dementia in hospital. Background: People with dementia are frequent consumers of health care and often have a poor experience in hospital but have been largely excluded from direct participation in research until recently. Limited understanding of the specific communication needs of people with dementia restricts access to the person's viewpoint. Recommendations for interviewers which consider the specific requirements of people with dementia are presented. Design/Method: This is a discursive article drawing on the experience of interviewing people with dementia in three separate studies. The conclusions that will be discussed are recommendations for researchers which were formulated following examination of the reflective journals written during the data collection phases of the studies and analysis of the data from the perspective of interviewer performance. Results: Six main issues have been identified and discussed with reference to Habermas's theory of communicative action. Conclusions: Interviewing people with dementia requires specific skills including an ability to be emotionally sensitive and respectful of the person. This engagement can be challenging and complex for the interviewer. It is vital that genuine engagement and mutual recognition are established before the interview is attempted. A more meaningful research outcome is likely to be the result. Relevance to clinical practice: The suggestions outlined here are relevant to a variety of people who are in contact with people with dementia in clinical settings. Developing the skills of researchers in this area needs a commitment by organisations to promote the inclusion of the perceptions of people with dementia in research and in discussions about their own care.